Research handbook on the EU's common foreign and security policy - Blockmans, S. F., 1973-; Koutrakos, Panos; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
At a critical time for the identity and policy direction of the EU, this Research Handbook examines the dynamics behind the development of the Common Foreign and Security Policy (CFSP) and the Common Security and Defence Policy (CSDP). The Research Handbook includes chapters from renowned experts that examine the efficacy and visibility of the EU as a diplomatic, military and civilian actor in a turbulent world. The authors' original contributions address the impact that existing frameworks, structures and procedures have on the effectiveness of the EU as an international actor and consider the legal challenges to the EU's integrated approach to external action. The Research Handbook on the EU's Common Foreign and Security Policy brings together academics and practitioners from different areas of law (EU and international law) and from the political science field. The interdisciplinary approach makes it essential reading for scholars of law, political science and international relations. Policymakers and all those with an interest in the external activities of the EU will also find this an insightful resource.
Introduction / Steven Blockmans and Panos Koutrakos -- Part A The law of CFSP/CSDP -- 1. The position of CFSP/CSDP in the EU's constitutional architecture / Marise Cremona -- 2. The institutional framework, legal instruments and decision-making procedures / Stephan Marquardt -- 3. Representing the EU in the area of CFSP: legal and political dynamics / Hylke Dijkstra and Peter Van Elsuwege -- 4. 'The Good, the bad and the ugly': three levels of judicial control over the CFSP / Christophe Hillion and Ramses A. Wessel -- Part B The practice of CSDP -- 5. Civilian CSDP missions: 'the good, the bad and the ugly' / Ana E. Juncos -- 6. Military CSDP operations: strategy, financing, effectiveness / Daniel Fiott -- 7. Responsibility and liability for CSDP operations / Joni Heliskoski -- 8. Capabilities and CSDP: resourcing political will or paper armies / Simon Duke -- 9. Non-proliferation of weapons of mass destruction / Eileen Denza ---Part C The nexus between CFSP/CSDP and other external policies -- 10. The law and practice of EU sanctions / Christina Eckes -- 11. The nexus between the CCP and the CFSP: achieving foreign policy goals through trade restrictions and market access / Andrea Ott and Guillaume Van der Loo -- 12. EU development cooperation and the CFSP: mutual encroachment? / Morten Broberg -- 13. The CFSP-humanitarian aid nexus / Mireia Estrada Cañamares -- 14. The nexus between CFSP/CSDP and the area of freedom, security and justice / Panos Koutrakos -- 15. European neighbourhood policy: CFSP in disguise / Steven Blockmans -- 16. The nexus between Common Foreign and Security Policy and energy policy / Theodore Konstadinides and Deni Mantzari -- 17. The European Union as a cybersecurity actor / Jed Odermatt -- 18. EU external health security policy and law / Anniek de Ruijter -- Part D Reflection on perspectives -- 19. The European Union as post-national realist power / Achilles Skordas ---20. Too much, too little, too late?: reflections on law and ethics in the EU's foreign policy / Jan Klabbers -- 21. The European Union's foreign policies: an external examination of the capabilities-expectations gap / Urfan Khaliq -- Conclusions / Steven Blockmans and Panos Koutrakos -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Evropská unie; zahraniční politika; bezpečnostní politika; foreign policy; security policy; země Evropské unie; European Union countries; e-knihy online; e-books online